Research and intervention in sport psychology: New perspectives for an inherent conflict - Kellmann, M.; Beckmann, J. (International Journal of Sport and Exercise Psychology, 2003)
Most research publications in sport psychology are of only limited use for solving the practical problems of athletes and coaches. This paper focuses on two major problems responsible for this apparent gap between research and its application. First, most studies in applied settings are conducted for research purposes only. Second, the transfer of sport psychological knowledge gained in laboratory and field studies to actual applications is impeded by limitations due to settings, study design, artificial performance tasks, and nonathletic samples. A problem-centered approach is proposed that could bridge this gap by integrating applied research and intervention. Action research provides an example for such a solution. This procedure enhances the acceptance of sport psychological interventions and subsequently improves their quality.